HUBUNGAN PENGETAHUAN TENTANG MANFAAT KOLOSTRUM TERHADAP KEJADIAN STUNTING PADA BALITA DI PUSKESMAS GARUDA PEKANBARU - Wiwi Sartika; Sara Herlina; Siti Qomariah (Universitas Prima Indonesia, 2024)
Stunting is a public health problem that is associated with an increased risk of morbidity, death, and barriers to motor and mental growth (Rahmadhita, 2020). The incidence of stunting has increased from year to year. Global data shows that the incidence of stunting in 2018 is estimated at 21.9% or 149 million children under 5 years of age, while in Southeast Asia there are 14.4 million children under 5 years of age experiencing stunting. The aim of this research is to find out the relationship between knowledge about colostrum and the incidence of stunting at the Garuda Pekanbaru health center. This research is an analytical observational study with a cross-sectional design. The research population was all mothers who brought their toddlers to the Garuda Health Center, with a sampling technique using the accidental sampling method of 225 samples. This research was carried out at the Garuda Community Health Center from June to December 2023. The instruments used were a questionnaire and height measurement. Data collection techniques involve approaching respondents to obtain their consent as research objects. Data was collected through a questionnaire regarding demographic data and history of breastfeeding, followed by observation of the child's height adjusted for age using a z-score table. Based on the chi-square statistical test, a value of p=0.000 was obtained, which shows that there is a relationship between knowledge about the benefits of colostrum and the incidence of stunting in toddlers. It is recommended that mothers exclusively breastfeed according to the child's nutritional needs to prevent stunting. Key words: Toddlers, Colostrum, Stunting